Youths, precariousness and cohabitation ethics: educational implications of the differential distribution modes of precariousness (Revista Contexto & Educação, 2023)
The article deals with the ways in which contemporary youths in Brazil have been framed by a wide and diverse set of media discourses about their subjective constitution. Sometimes entangled by the potential of being a Millennial and enjoying a different social environment, sometimes challenged by the construction of a reading of the youth condition marked by the lack, as is the case of “nem-nem-nem”, it was possible to diagnose certain ways of differential distribution of precariousness in the constitution of these subjective figures. Under the inspiration of the political writings of Judith Butler, we point to the advent of agendas that seem to extrapolate identity issues and move towards a collective struggle and organization in favor of a policy of singularity. Objectively, then, analytical centrality will be attributed both to the educational implications of this differential allocation of precariousness and to the different political and normative frameworks of this issue, as well as to the possibilities of youths to create new alliances from precariousness in favor of an ethics of cohabitation.
Keywords: Education. Youth. Precariousness. Brazil.